The Influence of Online Learning Quality on Students' Learning Stress - Abdul Hafiz Fajri; Sudarmin Sudarmin; Sri Wardani; Deni Setiawan (International Journal of Active Learning, 2023)
The research objective of this scientific article is to find out whether there is an effect of the quality of online learning on the learning stress of students at MIN 03 Central Lombok. This research uses a quantitative approach with the type of ex post facto. The instruments used in this research are observations and questionnaires. The population and sample in this study were all students of Class V MIN 03 Central Lombok, a total of 50 students. The results of this study indicate that there is an effect of the quality of online learning on the learning stress of students at MIN 03 Central Lombok. This is based on the results of data analysis, it is known that the F_count value = 165.79, with a significance level of 0.05, it can be used to predict the variable quality of online learning (X) and the learning stress variable (Y) . The magnitude of the correlation value (R) is equal to 0.881. From this output, the coefficient of determination (R Square) is 0.775 which implies that the effect of the independent variable on the dependent variable is 77.5%. Then the magnitude of the contribution or balance of online learning and learning stress is 75%. The remaining 25% is determined by other variables. So the results of this study indicate that there is an effect of the quality of online learning on learning stress.